Differential Pedogenesis of Some Pseudo-Andic and Non-Andic Soils in a Toposequence of Andaman and Nicobar Islands - Siladitya Bandyopadhyay (Journal of the Indian Society of Soil Science, 2022)
A large scale soil survey with high resolution image data and classification has been conducted to understand soil genesis of North and Middle Andaman district soils with emphasis of some pseudo-Andic and non-Andic nature in a topographical sequence for the first time. The study of soils showed sandy loam to silty clay loam texture, low in bulk density (0.96-1.22 Mg m-3) very strongly acidic (pH 4.6) to strongly alkaline (pH 9.0) with medium to high (7.4-9.8 g kg-1) organic carbon. Bulk density has a significant negative correlation with Feo (r = -0.74**), Feo/Fed (r = -0.77**) and Alo+0.5Feo (r = -0.73**), indicating the direct influence of amorphous Fe and Al on lowering bulk density of soils. Cation exchange capacity (CEC)/clay has also significant negative correlation with Feo (r = -0.53**), Feo/Fed (r = -0.60) and Alo+0.5Feo (r = -0.52**). Bulk density, acid oxalate extractable Fe (Feo) and Al (Alo), citrate-bicabonate-dithionate extractable Fe (Fed), percentage of Alo plus half the Feo and Feo/Fed ratio were proven to be the appropriate indicators of Pseudo-Andic properties in soils. Pseudo-Andic soils were classified as Aquandic Fluvaquents in interspersed valleys, Aquandic Endoaquepts in coastal plains and Aquandic Endoaqualfs in volcanic mudflats. Non-Andic soils were formed in uplands (Typic Hapluudalfs) and alluvial plains (Typic Endoaqualfs). The study inferred that effect of volcanic ejections was very much prominent in coastal plains, mangroves and swamps and has been spread up to the interspersed valleys. Soils on uplands and alluvial plains did not experience little or no influence of volcanic eruptions and found matured profiles. Soils on coastal region were environmentally most vulnerable and needs appropriate conservation measures. Vulnerability of coastal plain soils and typical pseudo-Andic soils observed require a special soil and land management to protect and maintain soil health and productivity. Criteria used to characterize the nature and vulnerability risk helps to manage similar kind of soils elsewhere for land use plan.